(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Through an analysis of projects developed by Edward Gordon Craig, Loie Fuller, David Tudor and Klaus Obermaier, this article discusses the discoursive and technológical pressupositions of an poetics of performatization of space. It problematizes the implications for human agency when performance space is constructed so that the human being is inscribed into its dinamics in such a way that his/her agency is submitted to the discoursive logics of this space by means of an technology designed to know no boundaries anymore.